Thaharah and Gen-Z Socialization - Suhardin, Suhardin (Blantika: Multidisciplinary Journal, 2025)
This research aims to determine the influence of thaharah in social ethics among generation Z by using an ex post facto survey model to measure social ethics scoring in the generation Z group who have high and low thaharah, developing an instrument for thaharah and social ethics for generation Z. Researchers found that generation Z who have high thaharah have high social ethics scores compared to generation Z who have low thaharah. The research conclusion is that cleanliness has a significant influence on social ethics among generation Z. Thaharah is not only clean physically, bodily and biologically, but also influences the soul, psychology and socio-cultural aspects of the social system.